2020
DOI: 10.21203/rs.3.rs-44522/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The experiences of adult patients receiving treatment for femoral shaft fractures at Kamuzu Central Hospital, Malawi: a qualitative analysis

Abstract: Background: There is a growing burden of musculoskeletal trauma in Malawi, and a lack of surgical capacity to manage common, debilitating injuries like femoral shaft fractures (FSFs). Non-operative treatment with skeletal traction remains the standard of care, with surgery available only at central hospitals. Patients experience myriad barriers to care, which can result in delayed treatment and complications. We sought to understand how patients navigate the Malawian health system and the barriers they face wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…In some instances, patients were forced to unenroll schoolaged children from school. Agarwal-Harding et al similarly found that patients with femoral shaft fracture in Malawi face numerous social and financial challenges following injury 16 . This is consistent with previous studies demonstrating the potential multigenerational repercussions of trauma that can push patients into vicious cycles of poverty and hardship 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some instances, patients were forced to unenroll schoolaged children from school. Agarwal-Harding et al similarly found that patients with femoral shaft fracture in Malawi face numerous social and financial challenges following injury 16 . This is consistent with previous studies demonstrating the potential multigenerational repercussions of trauma that can push patients into vicious cycles of poverty and hardship 6 .…”
Section: Discussionmentioning
confidence: 99%
“…While the gold standard treatment of femoral shaft fracture worldwide is surgical fixation with an intramedullary nail, this treatment is only feasible in Malawian CHs, where https://dx.doi.org/10.4314/mmj.v35i3.2 inadequate supply of implants, limited operating theatre (OT) time, lack of anesthesia staff, and insufficient surgical staff can limit its availability to all patients. Due to a lack of surgeons, inadequate surgical infrastructure, and limited resources, many femoral shaft fractures in Malawi are treated nonoperatively with skeletal traction, requiring prolonged hospitalization 5,11,16,17 . Unfortunately, no district or central hospital in Malawi has the minimum required resources to safely treat femoral shaft fractures and all hospitals reported some barriers to providing skeletal traction as a result of resource, staffing, and infrastructure limitations 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation